Clonal propagation of coconut:improved culture conditions for rhyzogenesis - Fernando, S.C.; Gamage, C.K. (Coconut Research Institute of Sri Lanka. Lunuwila, 1994)
Emphasis has recently been placed on improving culture conditions at the rooting stage of the coconut (cocos nucifera L) cloning procedure. In these experiments shoots for rooting were obtained by culturing shoot apices.

The effect auxins (IAA,NAA,IBA), carbohydrate sources (glucose, fructose, sucrose), lighting conditions and dark treatment on rooting were tested. Dip treatment of shoots in 10-4 M IAA solution for three to seven days followed by transfer to auxin free medium produced the best rooting (62.5 per cent). Addition of glucose at 60 g1-1 into the culture medium as the carbohydrate source increased the rooting percentage (71.4 per cent) nd stimulated secondary root formation. Sucrose at 60 gl-1 produced a higher number of primary roots per shoot (4,4) compared to roots per shoot inthe 60 gl-1 glucose treatment (2.3). Exposure of shoots to an initial seven-day dark period and localized lighting had a positive effect on rooting.

these findings can now be applied to obtain better rooting not only in clonal plants but also in zygotic embryo cultured plants.
Keywords: Biological Sciences; Tissue culture